Mechanisms and otoprotective strategies of programmed cell death on aminoglycoside-induced ototoxicity - Han, Lei; Wang, Zijing; Wang, Daqi; Gao, Ziwen; Hu, Shaowei; Shi, Dazhi; Shu, Yilai (Frontiers in Cell and Developmental Biology, 2024)
Aminoglycosides are commonly used for the treatment of life-threatening bacterial infections, however, aminoglycosides may cause irreversible hearing loss with a long-term clinical therapy. The mechanism and prevention of the ototoxicity of aminoglycosides are still limited although amounts of studies explored widely. Specifically, advancements in programmed cell death (PCD) provide more new perspectives. This review summarizes the general signal pathways in programmed cell death, including apoptosis, autophagy, and ferroptosis, as well as the mechanisms of aminoglycoside-induced ototoxicity. Additionally, novel interventions, especially gene therapy strategies, are also investigated for the prevention or treatment of aminoglycoside-induced hearing loss with prospective clinical applications.